2021
DOI: 10.1186/s12966-021-01203-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding children’s preference for park features that encourage physical activity: an adaptive choice based conjoint analysis

Abstract: Background Parks are a key setting for physical activity for children. However, little is known about which park features children prefer and which features are most likely to encourage them to be active in parks. This study examined the relative importance of park features among children for influencing their choice of park for engaging in park-based physical activity. Methods Children (n = 252; 8-12 years, 42% male) attending three primary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…As previously indicated, children living in the neighborhoods (1250 m street-network buffer) with the highest number of playgrounds could achieve 22 min more of TPA per weekday. As is known, the availability of playgrounds can be positively related to PA in children [ 20 , 21 , 22 , 23 ]. Our findings concur with a previous Australian study [ 21 ], showing that the upgrade of a park, including an all-abilities playground (among other park improvements), was related to an increase in park visitation among children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously indicated, children living in the neighborhoods (1250 m street-network buffer) with the highest number of playgrounds could achieve 22 min more of TPA per weekday. As is known, the availability of playgrounds can be positively related to PA in children [ 20 , 21 , 22 , 23 ]. Our findings concur with a previous Australian study [ 21 ], showing that the upgrade of a park, including an all-abilities playground (among other park improvements), was related to an increase in park visitation among children.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the park attractiveness would be more related to the park use than the distance. Furthermore, current evidence shows that the presence of certain features within parks, such as playgrounds, is related with PA among children [ 20 , 21 , 22 , 23 , 24 ]. In line with this idea, a study from Australia [ 47 ] indicated that the presence of playgrounds at the nearest public open space to home was positively related to children’s MVPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One key finding of this study is that despite proximity to parks and other sports facilities, the parents demonstrated extreme reluctance to allow park visitation in their absence. It must be noted that this finding is not unique to ME parents, and while most of the previous literature has concerned children younger than 13 years of age, these concerns are not being voiced by the parents of adolescents as well [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Reluctance to allow unaccompanied park visits has been reported to be more pronounced in socioeconomically disadvantaged areas.…”
Section: Discussionmentioning
confidence: 86%
“…A previous study concluded that motivation for being active outdoors was positively associated with the amount of space provided (Islam et al, 2016 ). Other studies of children’s park use have shown that the variety of play equipment and opportunities for children’s play are positively associated with use and PA (Cohen et al, 2020 ; Sylvester et al, 2014 ; Veitch et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%